Does Marriage Require Knowledge? Experiences of Women Participating in Pre-Marriage Education (UIN Sayyid Ali Rahmatullah Tulungagung, Indonesia, 2021)
Today the phenomenon of getting married at a young age is rising and shown through social media. According to Islamic religious rules, there are many pros and contras against this phenomenon, especially related to marriage. It has led to various pre-marriage educational programs as a means of understanding and preparing for marriage. This study aimed to explore the experiences of a single woman in emerging adulthood who participates in Pre-Marriage Talk Class. This study used a qualitative approach with the snowball sampling technique. A total of 5 respondents participated in this study, and data were collected through an online interview. The respondent’s answers were then analyzed thematically. The results showed that Pre-Marriage Talk Class provides additional knowledge, awareness, and mindset to participants, including 1) knowledge about the age of marriage; 2) knowledge about the vision and mission of getting married; 3) awareness of knowing the self; 4) knowledge of managing the self and environment, and 5) changing mindset. From the results, we can conclude that Pre-Marriage Talk Class is a suitable program for emerging adults who want to gain knowledge and skills related to themselves, how to manage self and environment, as well as an overview of the dynamics of married life that can be anticipated